Description of complete basic immunization coverage among infant - Farid Agushybana; Syamsulhuda BM; Sutopo Patria Jati; Martini Martini; Ayun Sriatmi (Intelektual Pustaka Media Utama, 2019)
Immunization coverage in every city/regency must be conducted in accordance with the standard coverage to suppress infectious diseases that can be prevented by vaccination. Temanggung regency is one of the cities/regencies in Central Java Province that have not reached 100% of village universal coverage immunization (UCI). The aim of this study was to determine the coverage of complete basic immunization in infants in Temanggung regency. The design of this study was descriptive observational with quantitative and qualitative approaches. The respondents of the research were parents having babies and the sample size was 520 children. The instrument used was the Rapid Card Check Form recommended by UNICEF. The results showed that there were still infants who had not been immunized. The reasons were that the infants had low birth weight, sick children during immunization, and no support from parents. As the immunization program aims to reduce infant and child mortality, parental awareness is important to increase immunization coverage in Temanggung regency.